Characteristic Soils "Soap" At Site Project Of Pekanbaru Mayor's Office - Joshua, Norman; Fatnanta, Ferry; Nugroho, S A (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Soil characteristic in field did not always meet specifications in planning to carrying out construction works . A good construction such as roads, buildings , and other construction will be able to last long if its supported by a good foundation soil ( Hartosukma , 2005) . One of the site project of Pekanbaru, there are soils are fragile when seen by direct eyes and can cause problems in the construction field. Therefore , the research would take up to study the characteristics of soils “soap” at the site project of Pekanbaru Mayor’s Office Development through the physical and mechanical properties of the soil type .Keywords: “ Soap ” Soils, Characteristics, Pekanbaru